2007
DOI: 10.1007/s11095-006-9210-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Approaches to Volume of Distribution Predictions: Understanding the Processes

Abstract: Generic distribution processes were identified as lipid partitioning and dissolution where the former is higher for lipophilic unionised drugs. In addition, electrostatic interactions with acidic phospholipids can predominate for ionised bases when affinities (reflected by binding to constituents within blood) are high. For acidic drugs albumin binding dominates when plasma protein binding is high. This ability to explain drug distribution and link it to physicochemical properties can help guide the compound s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
346
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(355 citation statements)
references
References 97 publications
9
346
0
Order By: Relevance
“…The volume of distribution at steady state was calculated by the tissue partition coefficient using the equation described by the Rodgers et al 17, 18. and the Rodgers & Rowland19, 20 methods considering the rapid equilibrium between blood and tissues.…”
Section: Methodsmentioning
confidence: 99%
“…The volume of distribution at steady state was calculated by the tissue partition coefficient using the equation described by the Rodgers et al 17, 18. and the Rodgers & Rowland19, 20 methods considering the rapid equilibrium between blood and tissues.…”
Section: Methodsmentioning
confidence: 99%
“…For comparison, V ss was also calculated according to the tissue composition equations proposed by Poulin and Theil (2002) and Rodgers and Rowland (2007). These tissue composition equations are considered to be mechanistic alternatives to interspecies scaling and facilitate the use of physiologically based pharmacokinetic models in the absence of in vivo tissue distribution data.…”
Section: Berry Et Almentioning
confidence: 99%
“…The present work aims to do so. Finally, interspecies scaling methods were compared with the mechanistic tissue partition methods for prediction of human V ss proposed by Poulin and Theil (2002) and Rodgers and Rowland (2007).…”
Section: Introductionmentioning
confidence: 99%
“…In order to estimate the unknown association constants, Rodgers et al suggested to determine K A,AP for the erythrocytes from the blood-plasma ratio B : P and use this value as an approximation for the association constants in the other tissues. For details see (12,26). Parameter values can be found in (12,16) for the species rat.…”
Section: Resultsmentioning
confidence: 99%
“…(13)). Parameter values can be found in (16,26) for the species rat. In their seminal papers in 2000/01 (13,14), Poulin and Theil proposed an in silico approach to a priori predict tissue-plasma partition coefficients solely based on few compound specific in vitro data.…”
Section: Very Weak Bases Neutrals Acids and Type 2 Zwitterionsmentioning
confidence: 99%